Antibiotic resistance patterns of Escherichia coli and Salmonella Spp. isolated from pork at retail markets in Northern Vietnam - Truong Ha Thai; Chu Thi Thanh Huong; Vu Thi Thu Tra; Truong Lan Oanh (2021)
Antimicrobial resistance has become a global health problem for both humans and animals because of the increase in treatment failure for infections. This study was conducted to determine the prevalence and antibiotic resistance patterns of Escherichia coli and Salmonella spp. from retailed pork in Northern Vietnam. In total, 152 pork samples were collected from 60 retail markets in the northern part of Vietnam. E. coli and Salmonella isolates were tested for antimicrobial susceptibility against 15 antibiotics. The prevalence of E. coli and Salmonella spp. in pork were 58.55% and 30.26%, respectively. Majority of E. coli isolates were resistant against tetracycline (62.9%) followed by streptomycin (49.4%), trimethoprim (48.3%), and ampicillin (47.2%). Multidrug resistance was found in 92.19% of E. coli resistant isolates. Similarly, Salmonella isolates showed the highest rate of resistance to tetracycline (78.3%), followed by streptomycin (60.9%), chloramphenicol (56.5%), and trimethoprim (52.2%). Multidrug resistance was found in 84.21% of Salmonella resistant isolates. In conclusion, the study demonstrated high prevalence and multidrug resistance of both E. coli and Salmonella isolated from pork in the study area. The findings indicate a strong need to improve good hygiene practices and the prudent use of antibiotics in swine farms.
Keywords: Resistance to antibiotics; Escherichia coli; Salmonella